ANALISIS PENYEBARAN KEMISKINAN KABUPATEN/KOTA DI SUMATERA - Yunita Ariani Zebua; Fajar Restuhadi; Syaiful Hadi (Program Pascasarjana Universitas Riau, 2017)
Poverty is one Fundamental issues serious concern which become from the government. An important aspect of supporting poverty tackling strategies is the provision of accurate and targeted poverty data. BPS presents data set and poverty information and indicators related to poverty issues in level regency/city and province. The island of Sumatra is the region with the densest population after Java with the distribution of poverty of 21.6%. The purpose of this research was to analyze of poverty factors spreading of regencies/cities in Sumatera to formulating appropriate policies. The research consist of 6.468 cell data covering 154 regencies/cities in Sumatera and 42 poverty indicators which are processed with factor analysis. The research results showed that the factors of poverty of the Regency and City in Sumatera were: 1) economic factors, employment and housing facilities, 2) under-five health factors, 3) factors of labor and clean water facilities, 4) social factors, 5 ) Maternal health factors, education and government facilities. Therefore, in formulating the policy, the government should pay attention to the things that are done in poverty alleviation was to pay attention to the factors causing poverty that existed each region of the Regency / City.